The impact of different types of shift work on blood pressure and hypertension - Madeira, Sara Gamboa (2021)
Funding Information: This work was supported by the Ph.D. research Grant PDE/BDE/127787/2016 from Funda??o para a Ci?ncia e Tecnologia (FCT) /Fundo Social Europeu. Funding Information: Funding: This work was supported by the Ph.D. research Grant PDE/BDE/127787/2016 from Fundação para a Ciência e Tecnologia (FCT) /Fundo Social Europeu. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.